METODE ANALISIS PENGUKURAN KINERJA KEUANGAN PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Kristianto, Djoko - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
Abstract One purpose of investors to invest is to obtain the return. Stocks are selected investment instruments that many investors because the stock is able to provide the level of profit. Stock prices reflect the value of a company. If the company achieve a good performance, the company's stock will be much in demand by investors. Accomplishments achieved either company can be seen in the financial statements published by the company issuer. Issuer is obliged to publish financial statements in certain periods. This financial report is useful for investors to assist in making investment decisions, like selling, buying, or planting stock. In general, financial performance measurement is done by using Return On Investment (ROI), Earnings Per Share (EPS) and Return On Equity (ROE). In addition to using the financial performance analysis, financial analysis method newly developed for the measurement of performance is the Economic Value Added (EVA) and Market Value Added (MVA). Keywords: Return On Investment, Earnings Per Share, Economic Value Added dan Market Value Added